A highly stable microporous covalent imine network adsorbent for natural gas upgrading and flue gas CO2 capture - Das, Swapan K.; Wang, Xinbo; Ostwal, Mayur M.; Lai, Zhiping (Separation and purification technology, 2016)
The microporous CIN material offering superior chemical robustness under both acidic and basic conditions and high thermal stability. Framework enriched with Lewis basicity and high Qst facilitated to enhance natural gas upgrading and flue gas CO2 capture, make the material as a promising adsorbent. [Display omitted] •A covalent triazine-piperazine linked polymer with permanent porosity.•Outstanding chemical robustness and high thermal stability.•Enhanced CO2 and CH4 uptake and high CO2/N2 and CH4/N2 selectivity.•High heats of adsorption for CH4 and CO2. The feasible capture and separation of CO2 and N2 from CH4 is an important task for natural gas upgrading and the control of greenhouse gas emissions. Here, we studied the microporous covalent imine networks (CIN) material prepared through Schiff base condensation and exhibited superior chemical robustness under both acidic and basic conditions and high thermal stability. The material possesses a relatively uniform nanoparticle size of approximately 70–100nm. This network featured permanent porosity with a high surface area (722m2/g) and micropores. A single-component gas adsorption study showed enhanced CO2 and CH4 uptakes of 3.32mmol/g and 1.14mmol/g, respectively, at 273K and 1bar, coupled with high separation selectivities for CO2/CH4, CH4/N2, and CO2/N2 of 23, 11.8 and 211, respectively. The enriched Lewis basicity in the porous skeletons favours the interaction of quadrupolar CO2 and polarizable CH4, resulting in enhanced CH4 and CO2 uptake and high CH4/N2, CO2/CH4 and CO2/N2 selectivities. Breakthrough experiments showed high CO2/CH4, CH4/N2 and CO2/N2 selectivities of 7.29, 40 and 125, respectively, at 298K and 1bar. High heats of adsorption for CH4 and CO2 (QstCH4; 32.61kJmol−1 and QstCO2; 42.42kJmol−1) provide the ultimate validation for the high selectivity. To the best of our knowledge, such a versatile adsorbent material that displays both enhanced uptake and selectivity for a variety of binary gas mixtures, including CO2/CH4, CO2/N2 and CH4/N2, has not been extensively explored.